2014
DOI: 10.1111/chd.12222
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Exercise Variables in 335 Patients after the Fontan Operation: A 23-year Single-center Experience of Cardiopulmonary Exercise Testing

Abstract: Fontan patients exhibit markedly impaired CPX variables, and all the major variables, especially peak VO2 , predicted the risk of both morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 42 publications
3
56
2
1
Order By: Relevance
“…With approximately 63% of peak oxygen uptake in contrast to controls, our _ VO 2peak values concur with results from other studies [4,13,21,22]. In line with previous findings [9,16], Fontan patients differ from controls in that time spent in MVPA correlated significantly with _ VO 2peak values.…”
Section: Cpet and Mvpasupporting
confidence: 92%
“…With approximately 63% of peak oxygen uptake in contrast to controls, our _ VO 2peak values concur with results from other studies [4,13,21,22]. In line with previous findings [9,16], Fontan patients differ from controls in that time spent in MVPA correlated significantly with _ VO 2peak values.…”
Section: Cpet and Mvpasupporting
confidence: 92%
“…Cardiopulmonary exercise tolerance decreases greatly over the life span of Fontan patients 17 28 33 34. In a large study 321 adult Fontan survivors had cardiopulmonary exercise testing and were then observed for the combined study end point of death or transplantation or cardiac hospitalisation over 21 months.…”
Section: Predictors Of Long-term Mortalitymentioning
confidence: 99%
“…In a large study 321 adult Fontan survivors had cardiopulmonary exercise testing and were then observed for the combined study end point of death or transplantation or cardiac hospitalisation over 21 months. Though almost all peak exercise and anaerobic threshold parameters (VO 2 , % of predicted VO 2 , heart rate reserve, anaerobic threshold, minute ventilation (VE)/carbon dioxide production (VCO 2 slope), were able to predict unscheduled cardiovascular hospital admissions, only peak VO 2 was able to independently predict mortality HR=0.88 for each 1% increase in peak VO 2 17. Another study showed that a peak VO 2 of <16.6 mL/kg/min and peak-exercise heart rates of <122.5 bpm were predictors for long-term mortality with an HR=7.5, CI 2.6 to 21.6 and HR=10.6, CI 3 to 37.1, respectively.…”
Section: Predictors Of Long-term Mortalitymentioning
confidence: 99%
“…Cardiopulmonary exercise testing (CPET) assesses exercise capacity in adults and children in healthy and chronic conditions . CPET measures oxygen uptake, cardiac, and skeletal muscle performance, and respiratory parameters during incremental exercise up to voluntary exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…6 Cardiopulmonary exercise testing (CPET) assesses exercise capacity in adults and children in healthy and chronic conditions. 7,8 CPET measures oxygen uptake, cardiac, and skeletal muscle performance, and respiratory parameters during incremental exercise up to voluntary exhaustion. Two case series of four adult Pompe patients assessed exercise capacity using CPET before and 12-36 months after ERT, and revealed improvement of peak work load and oxygen uptake after ERT.…”
mentioning
confidence: 99%